Golf swing in response to anteroposterior ball position - Kim, S. E.; Lee, J.; Lee, S. Y.; Lee, H.-D.; Lee, S.-C.; Shim, J. K. (International Journal of Sports Science & Coaching, 2023)
Studies for effective golf coaching such as providing a causal relationship between the address posture and golf-swing behaviors are limited. This study investigated the effects of ball position on golf-swing behaviors. Twenty professional golfers performed golf swing at five different anteroposterior (forward/backward) ball positions: reference ball position (R0) and ±2.14 cm (golf ball radius) and ±4.17 cm (golf ball diameter) to the R0. Their swings were captured using a motion capture system with two force platforms. Statistical parametric mapping was used to compare the ground reaction forces and swing kinematics for different ball positions. The backward (closer to the golfer) ball positions were associated with more extended trunk, knee, and ankle angles in the sagittal plane during the entire golf swing (from address to impact) compared to that of the R0. The backward ball positions were generally associated with decreased horizontal ground reaction forces and pelvis and X-factor angles in the transverse plane during the downswing compared to that of the R0. Whereas, these patterns were reversed for the forward ball positions. These results demonstrate the value of ball position for coaching methods including the importance of a consistent ball position and reveal a consistent human control system for professionals which can provide valuable information for modeling the features of a digitized coaching tool.